Diskriminasi dalam Kerja Kelompok : Studi Kasus Mahasiswa Bimbingan Penyuluhan Islam di Universitas Islam Negeri Sumatera - Ainul Mardiyah; Dira Kaniya; Dwi Putri Lestari (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
The phenomenon of discrimination in group task distribution within higher education remains a social issue that rarely receives serious attention, particularly within the Islamic Guidance and Counseling department. This study aims to identify the forms, causes, and potential solutions to discrimination experienced by students in group work contexts. Employing a descriptive qualitative method, data were collected through interviews with four informants. The findings reveal that discrimination arises due to stereotypes, unequal contributions, personal conflicts, and weak group communication. Proposed solutions include random group assignments, clear initial agreements on task distribution, and individual contribution assessments. These findings underscore the importance of instilling values of justice, inclusivity, and collaborative ethics in higher education learning environments.